« Plädoyer für das Chaos » ? Les mutations de la littérature allemande pour la jeunesse autour de 1968 - Mathilde Lévêque (Strenae)
The student protest movements of 1968 and the cultural shift they set in motion throughout West German society profoundly changed children's literature, through its themes, forms and functions. While the rupture is clear, it is still necessary to try to understand what preceded, explained and shaped this rupture. The notion of a rupture, gap, or fracture corresponds to a reality with multiple dimensions: what is broken and why? What past norms does it intend to overthrow? If chaos entails, what is it and what does it mean?